Appendix appendix : a proposal for a TV series - Gander, Ryan; Bailey, Stuart (Zürich : JRP/Ringier, 2007)
Artist's book containing a proposal and scripts for a television series that will use fine art, TV, film, literature, cartoons, etc. to create a conceptual art work
boek